Wilms’ tumor 1 protein expression in embryonal and alveolar rhabdomyosarcoma and its association with clinical prognostic factors: a cross-sectional study (Medical Journal of Indonesia, 2020)
BACKGROUND Embryonal rhabdomyosarcoma (ERMS) and alveolar rhabdomyosarcoma (ARMS) are the two major histological types commonly found in the pediatric population, which have different morphology and genetic profile. Wilms’ tumor 1 (WT1) is an antigen highly expressed in solid tumors, including rhabdomyosarcoma, and a potential immunotherapy target. Only a few studies have attempted to determine WT1 expression in rhabdomyosarcoma. This study was conducted to demonstrate WT1 expression in ERMS, ARMS and associate it with established prognostic factors. METHODS A cross-sectional study was conducted at the Department of Anatomical Pathology, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital, Jakarta using archival data from January 2011 to December 2017. 30 from 102 ERMS cases and 16 from 28 ARMS cases were included in this study. Data of age, tumor size, and location were collected. All cases were stained by WT1 immunohistochemistry. The expression was assessed semiquantitatively using histoscore (H-score) formula. An independent t-test was used to compare WT1 expression between ERMS and ARMS. Correlation analysis was used to evaluate the relationship between WT1 expression and prognostic factors. RESULTS All ERMS and ARMS cases expressed WT1 in diffuse, moderate to strong staining. ERMS show higher WT1 expression than ARMS (H-score 179.9 versus 149.5) (p = 0.014). Strong WT1 expression mostly found in patient age <20 years and non favourable location. Moderate WT1 expression mostly found in cases with tumor size >5 cm. CONCLUSIONS WT1 expression was higher in ERMS cases than in ARMS cases, which the expressions were similar in different age, tumor size, and location groups.